2021
DOI: 10.21608/ejvs.2021.94025.1277
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Food Poisoning Escherichia coli (STEC) in Ready-to-Eat Meat Products in Aswan, Egypt

Abstract: R EADY to eat meat was defined as case of meat being ready for immediate consumption.Food diseases of microbial origin are associated with serious health problems due to consumption of ready to eat meat and meat products in many places in the world. Conventional processing methods used in preparation, improper storage / conservation are the main factor contributing to food contamination. One of the common pathogenic bacteria that causes the food-borne diseases is E. coli .Some strains produce toxins that can l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Our study shows that >¼th of RTE foods assessed from Yenagoa, Nigeria had a poor microbiological quality was far lower than the 72.3–85% report from Mexico [ 2 , 52 ], 69% from Iran [ 53 ] and 39.2% from China [ 54 ]. Much lower reports compared to the findings from our study have been reported, such as 20.83% in North Africa [ 55 ], 8.3% in Vietnam [ 18 ], 3.1% in South America [ 4 ]. Comparisons of the E .…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our study shows that >¼th of RTE foods assessed from Yenagoa, Nigeria had a poor microbiological quality was far lower than the 72.3–85% report from Mexico [ 2 , 52 ], 69% from Iran [ 53 ] and 39.2% from China [ 54 ]. Much lower reports compared to the findings from our study have been reported, such as 20.83% in North Africa [ 55 ], 8.3% in Vietnam [ 18 ], 3.1% in South America [ 4 ]. Comparisons of the E .…”
Section: Discussioncontrasting
confidence: 95%
“…Castro-Rosas et al [ 2 ] detected EIEC in RTE salads. Mokhtar and Karmi [ 55 ] reported that 24% of their E . coli isolates were EHEC ( stx2 + eae ) with none of the entire isolates with stx1 gene, while other 64% of the isolates had the eae gene only, which was very high compared to the result of our study; also differ since both Shiga toxin gene was detected in 1 of our isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of E. coli was 21% in different RTE food samples collected from different sources in this study. Depending on culture, staining, and biochemical tests, a study in Egypt detected E. coli isolates in 12/30 (40%) samples of sausage, 4/30 (13%) of hamburger, 8/30 (27%) of minced beef, and 1/30 (3%) of fried chicken [7]. A study conducted in Tamil Nadu found mixed vegetable salad (80%), panipuri (70%), and veg cutlet (60%) revealed higher positive results for E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these foods are shelf-stable, flavorful, affordable, and immediately accessible to customers because they do not require a lengthy pre-treatment process [5,6]. The possibility of Escherichia coli to induce health risks occurs mainly during the preparation and storage of contaminated RTE meat [7]. However, because RTE Available at www.veterinaryworld.org/Vol.15/June-2022/12.pdf meats have been identified as transporters for foodborne bacteria such as E. coli, these foods provide a significant microbiological risk [8].…”
Section: Introductionmentioning
confidence: 99%